The Relationship between the Characteristics of the Board of Directors and the Organizational Performance in the Companies by Applying to the Yemeni Banks - Gamaan, Nagat (The Arab Journal of Administration, 2019)
The study problem is measure the relationship between the board of directors characteristics and performance Yemen Banks Case. The aim is to Identify the variables of the board of directors characteristics and to develop the proper regression models to examine the relationships between the board characteristics and bank performance. To achieve its objectives, the study used the panel data for 10 Yemeni banks for the years 2000-2013. The study also identified 13 independent variables and two financial dependent variables. The study used the econometric program EVIEWS for regression analysis models to test these relationships. The result shows that there are positive relationships between the numbers of meetings, CEO duality, salaries and compensation for the CEO, board members and ROE and ROA. In addition, result shows a negative relationship between the board size, and the ROE and ROA. The study recommends that banks to form effective BOD with good characteristics, central bank of Yemen encourages banks to provide regular data on the BOD variables, and encourage advancing women in the board.